2021
DOI: 10.1021/jacsau.1c00196
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Cu–Al–Oxo Extra-Framework Clusters for Selective Methane Oxidation on Cu-Exchanged Zeolites

Abstract: Cu-zeolites are able to directly convert methane to methanol via a three-step process using O 2 as oxidant. Among the different zeolite topologies, Cu-exchanged mordenite (MOR) shows the highest methanol yields, attributed to a preferential formation of active Cu–oxo species in its 8-MR pores. The presence of extra-framework or partially detached Al species entrained in the micropores of MOR leads to the formation of nearly homotopic redox active Cu–Al–oxo nanoclusters with the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 69 publications
(178 reference statements)
1
43
0
Order By: Relevance
“…Further, we can exclude Cu-Al-oxo extra-framework clusters as proposed by Lee et al having an outsize role in explaining our reported material differences as we used both NH 4 and H forms for the ion exchange with copper. 52 It did not lead to distinct activity trends (Table S5). Instead, we postulate that the acid site accessibility degree induced by the Al site distribution influences the reactivity of the subsequently formed Cu-oxo species.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Further, we can exclude Cu-Al-oxo extra-framework clusters as proposed by Lee et al having an outsize role in explaining our reported material differences as we used both NH 4 and H forms for the ion exchange with copper. 52 It did not lead to distinct activity trends (Table S5). Instead, we postulate that the acid site accessibility degree induced by the Al site distribution influences the reactivity of the subsequently formed Cu-oxo species.…”
Section: Resultsmentioning
confidence: 96%
“…Quantification of octahedral, extra-framework Al with 27 Al MAS NMR (Figure S8) resulted in largely the same amount for all synthesized MOR. Note that the discrepancy to the 1 H MAS NMR and DRIFTS data can be rationalized by the presence of small extra-framework Al clusters. , Furthermore, it is possible for some more distorted Al to be broadened beyond detection at this field strength. , …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This may occur in the zeolite samples as the framework structure restricts the location of O atoms around the cation sites. These XANES features have previously been used for analysis of the oxidation states of Cu species in zeolites including faujasite, ZSM-5, mordenite, ,, chabazite, MFI, and others . Additionally, the first derivative XANES data can be used to determine the oxidation state of the copper atoms present.…”
Section: Resultsmentioning
confidence: 99%